PENINGKATAN PARTISIPASI SISWA DALAM PEMILAHAN SAMPAH DENGAN PENDEKATAN 4R GUNA MENGURANGI PENUMPUKAN SAMPAH DI TPA - Al Fitri Chahyani; Siti Rokmanah; Nana Hendracipta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Waste is anything that is thrown away because it is no longer needed, and not needed. The problem is that many elementary school students still lack the knowledge to manage waste and sort waste by type. Even students who already understand have a tendency to litter. The purpose of this study was to increase elementary school students' awareness of the importance of disposing of waste properly and how to use the 4Rs approach to recycle waste materials into new products. Qualitative research using descriptive observational design was the methodology used. The research methodology was implemented through open-ended interviews, participant-led focus group discussions, literature review, and field survey. According to the research findings, a large number of students still lack knowledge about the different types of waste and how to dispose of them. One of the recommendations that can be given is to socialize to students about proper waste management so that they can utilize it and educate the community on how to utilize waste and minimize waste so that there is no accumulation of waste in landfills that can cause new problems or diseases.